Advances in Urban Green Development and Resilient Cities (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Global cities face rising socio-ecological pressures and driving forces of change. Among them, climate change highlights the need for better urban spaces to improve citizens' quality of life. Consequently, collaboration across disciplines is needed for resilient, future-proof urban solutions, involving scholars in different disciplines such as urban planning, green design, architecture, and agronomy. The published papers in this reprint address resilience through various approaches. Specifically, the concept of resilience is treated as a strategy to enhance urban sustainability and adaptability, focusing on "bounce-forward" solutions rather than just recovery from socio-ecological pressures and challenges. This approach integrates technical tools and interdisciplinary collaboration, emphasizing proactive measures in urban planning, green design, and the sustainable use of ecosystem services to create more resilient urban spaces. The goal is to create resilient urban environments that can withstand and adapt to future challenges such as climate change, social needs, and commercial pressures. This holistic and integrated approach to urban resilience​ focuses not just on recovering from disruptions but also on enhancing the urban systems to be better prepared for future challenges.